What 2 numbers add up to 1 and multiply to -12

Answers

Answer 1
Answer: -3 and 4......................
Answer 2
Answer: -3 * 4 = -12 
-3 + 4 = 1

Related Questions

Sophia has 3 pink tulips and 3 white tulips. what fraction of sophias tulips are pink
Doing monomials. How do you do this one?
PLS FINDD THIS THIS IS DUE IN 10 MINNNNNN!!! PLEASE DO WITH CLEAR STEPSS!!! I'LL MARK U BRAINLIEST
the difference between two positive integers is 40. one integer is three times as great as the other. find the integer.
What is the sum of the first 39 positive odd numbers?

A hot-air balloon is at an elevation of 4,800 feet if the balloon falls 40 feet per minute how long will it take for the balloon to reach 2000 feet

Answers

1. 4800-2000=2800
This is the distance that the balloon needs to fall to reach an altitude of 2000 feet.
2. 2800/40=70
Distance/rate=time
The answer is 70 minutes.

Solve the differential equation by separation of variables
x(dy/dx)=4y

Answers

get all your x one on side and y on the opposing sideso we have
xdy=4ydx
dy/y=4dx/x
integrate both sides
lny=4lnx+C
y=e^(4lnx+C)
The answer is y=cx^4

Calculate cos to two decimal places

Answers

Cos to 2 decimal places is -0.90

:)

An average human heart beats 60 times per minute. If an average person lives to the age of 75, how many times does the average heart beat in a lifetime?

Answers

The average heart beat in a lifetime is 2,365,200,00 beats.

Given that,

An average human heart beats 60times per minute.

If an averageperson lives to the age of 75.

We have to determine,

How many times does the averageheart beat in a lifetime.

According to the question,

An average human heart beats 60 times per minute.

And there is 60 beats in a minute and 60 minutes in an hour,

Then,

Heart beat per hour = 60 beats × 60 minutes = 3,600 beats per hour.

Then,

The amount of beats in an hour by the number of hours in a day.

Heart beats per day = 3600 × 24 hours = 86,400 beats per day

Then,

The number of days in a year is 365 in a year, but use the flat rate of 365 since that is generally the accepted answer.

Heart beat per year = 86,400 × 365 days = 31,536,000 beats per year

Therefore,

An average person lives to the age of 75,

Heart beat in a lifetime to age of 75 years,

= 31,536,000 × 75 years = 2,365,200,00 beats in a lifetime.

Hence, The average heart beat in a lifetime is 2,365,200,00 beats.

To know more about Average value click the link given below.

brainly.com/question/13820877

Answer:

The average number of beats in a lifetime would be 2,365,200,000

Step-by-step explanation:

To find the amount we need to take basic steps. The first step is multiplying the number of beats to find out how many are in an hour. Since there are 60 in a minute and 60 minutes in an hour, multiply the two.

60 beats * 60 minutes = 3,600 beats per hour.

Now multiply the amount of beats in an hour by the number of hours in a day.

3,600 * 24 hours = 86,400 beats per day

Now multiply the number of days in a year. Technically there is 365 1/4 in a year, but we'll use the flat rate of 365 since that is generally the accepted answer.

86,400 * 365 days = 31,536,000 beats per year

And now we take that number and multiply by the number of years that he lines

31,536,000 * 75 years = 2,365,200,00 beats in a lifetime

The radius of a cylindrical gift box is (2x+3) in. The height of the gift box is twice the radius. What is the surface area of the cylinder? Write your answer as a polynomial form.

Answers

let "r" be the radius of cylinder and "h" be the height.
Formula for surface area is:

S= 2*r^2*pi + 2*r*pi*h

where 2*4^2*pi is surface of two bases of cylinder and 2*r*pi*h is surface of mantle.
One of the tasks conditions is that h = 2*r.

S = 2*r^2*pi + 2*r*2*r*pi

second and last condition is r=(2x+3). Now we express this as well.

S = 2*(2x + 3)^2 * pi + 4*(2x+3)^2*pi=6*pi*(2x+3)^2

S = 6*pi*(4x^2+12x + 9)
S = 24*pi*x^2 + 72*pi*x + 54*pi

Factorise-              6y-15y^2
     HELP

Answers

We will take the common terms in the expressions-

Here in the expression, 3y is a common term.
So,

6y - 15y^(2)

3y(2 - 5y)

So, the answer is 3y(2 -5y)
6y-15y^2
3y(2-5y)                                                          (taking 3y as common)
clearly 3y(2-5y) cannot be factorised further hence this is the answer